Stabilization of new carbon inputs rather than old carbon decomposition determines soil organic carbon shifts following woody or herbaceous vegetation transitions - Eclesia, Roxana Paola; Jobbagy Gampel, Esteban Gabriel; Jackson, Robert B.; Rizzotto, Marcos Gregorio; Piñeiro, Gervasio (Springer, 2018)
Background and aims: Although numerous studies have quantified the effects of land-use changes on soil organic carbon (SOC) stocks, few have examined simultaneously the weight of carbon (C) inputs vs. outputs in shaping these changes. We quantified the relative importance of soil C inputs and outputs in determining SOC changes following the conversion of natural ecosystems to pastures or tree plantations, and evaluated them in light of variations in biomass production, its quality (C:N) and above/belowground allocation patterns. Methods: We sampled soils up to one-meter depth under native grasslands or forests and compared them to adjacent sites with pastures or plantations to estimate the proportion of new SOC (SOCnew) retained in the soil and the decomposition rates of old SOC (k SOC-old ) based on δ 13C shifts. We also analyzed these changes in the particulate organic matter fraction (POM) and estimated above and belowground net primary production (ANPP and BNPP) from satellite images, as well as changes in vegetation and soil’s C:N ratios. Results: The conversion of grasslands to tree plantations decreased total SOC contents while the conversion of forests to pastures increased SOC contents in the topsoil but decreased them in deep layers, maintaining similar soil stocks up to 1 m. Changes in POM were less important and occurred only in the topsoil after cultivating pastures, following SOC changes. Surprisingly, both land-use trajectories showed similar decomposition rates in the topsoil and therefore overall SOC changes were not correlated with C outputs (k SOC-old ) but were significantly correlated with C inputs and their stabilization as SOCnew (similar results were obtained for the POM fraction). Pastures although decreased ANPP (as compared to forest) they increased belowground allocation and C:N ratios of their inputs to the soil, probably favoring the retention and stabilization of their new C inputs. In contrast, tree plantations increased ANPP but decreased BNPP (as compared to grasslands) and scarcely accumulated SOCnew probably as a result of the high C retention in standing biomass. Conclusions: Our results suggest that SOC changes are mainly controlled by the quantity and quality of C inputs and their retention in the soil, rather than by C outputs in these perennial subtropical ecosystems.